2015
DOI: 10.1108/ijm-10-2012-0158
|View full text |Cite
|
Sign up to set email alerts
|

How to empower employees: using training to enhance work units’ collective empowerment

Abstract: Purpose -The purpose of this paper is to examine, theoretically and empirically, whether an employee training program can enhance the collective perception of empowerment of work units within an organization. The authors hypothesized that training participation relates to empowerment by enhancing the potency, meaningfulness, impact, and autonomy of the employees. Design/methodology/approachThe authors collected data at two time points, before and after the training intervention. Over the two periods, the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 33 publications
2
30
0
2
Order By: Relevance
“…An extensive training of newly established TTO staff via relevant workshops and short courses to ensure efficient functioning of the office as stated by participants in this study is partially supported by various studies [36][37][38][39]. These studies demonstrated the effectiveness of staff empowerment at work place via relevant workshops or courses.…”
Section: Extensive Training Of Technology Transfer Office Staffsupporting
confidence: 57%
“…An extensive training of newly established TTO staff via relevant workshops and short courses to ensure efficient functioning of the office as stated by participants in this study is partially supported by various studies [36][37][38][39]. These studies demonstrated the effectiveness of staff empowerment at work place via relevant workshops or courses.…”
Section: Extensive Training Of Technology Transfer Office Staffsupporting
confidence: 57%
“…2016, 8(2S), 1272-1286 1274 criteria (Wright, 2007 by Vogtlin et al in 2015 tilted as "how can we empower staff", they followed this hypothesis that training participation related to empowerment is correlated with increased power, effort, and independence of staff. The results showed a positive relationship between training participation and raising the psycho-social empowerment with different effects of empowerment dimensions (Voegtlin et al, 2015). Appropriate behavioral models of employees and directors create a strong incentive for staff.…”
Section: Introductionmentioning
confidence: 91%
“…Also increases of satisfaction with work. Besides, he says that training consequences on productivity of the worker are included also by excess of expectations, cross training of the personnel, training of employees for promotion, preservation of safe working environment and reduction of mistakes (Voegtlin, Boehm, & Bruch, 2015).…”
Section: Relationships Between Training and Employee Performancementioning
confidence: 99%